2013
DOI: 10.5137/1019-5149.jtn.8989-13.3
|View full text |Cite
|
Sign up to set email alerts
|

Local application of corticosteroids combined with surgery for the treatment of chronic subdural hematoma

Abstract: AIm: Combination treatment consisting of surgery and pre-or post-operative corticosteroids for chronic subdural hematoma (CSH) tend to have better outcomes than surgery only. However, there are many complications after long-term use of corticosteroids. In this study, we evaluated the clinical outcomes of local application of corticosteroids combined with surgery for CSH. mATERIAl and mEThods:We retrospectively analysed the data of the patients undergoing surgery and local application of Methylprednisolone Sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Stanisic et al showed significantly higher levels of proinflammatory mediators (interleukin-2 receptor, and interleukins 5, 6 and 7) and anti-inflammatory mediators in the cSDH fluid compared with systemic levels, as well as a higher ratio of pro-to anti-inflammatory mediators [15]. The contact between cSDH fluid and the dural border cells seems to evoke a local aseptic inflammatory and inflammation-induced angiogenic reaction [16]. This angiogenic reaction leads to the formation of neomembranes that cause repeated microbleeds into the haematoma cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Stanisic et al showed significantly higher levels of proinflammatory mediators (interleukin-2 receptor, and interleukins 5, 6 and 7) and anti-inflammatory mediators in the cSDH fluid compared with systemic levels, as well as a higher ratio of pro-to anti-inflammatory mediators [15]. The contact between cSDH fluid and the dural border cells seems to evoke a local aseptic inflammatory and inflammation-induced angiogenic reaction [16]. This angiogenic reaction leads to the formation of neomembranes that cause repeated microbleeds into the haematoma cavity.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that for some patients, steroids may be the only therapy required; however, there were complications from systemic corticosteroid use including hyperglycemia and gastritis 49 . Local, intrahematoma administration of steroids has been attempted by Xu et al 50 Twenty-six patients underwent hematoma evacuation and local application of methylprednisolone into the hematoma cavity. All patients were recurrence free, and none experienced complications related to the steroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Muramatsu et al treated four patients of recurrent CSDH with local herbal medicine, Gorei-san successfully without surgery. [20] [21] Retrospective case-control study 198 Corticosteroid Postoperative (methyl) prednisolone 0.5 mg/kg daily for 1 month Berghauser Pont et al, 2012 [22] Retrospective cohort study 496 Corticosteroid Extended preoperative corticosteroid administration Chan et al, 2015 [23] Randomized controlled study 248 Corticosteroid Dexamethasone 4 mg q6h for 4 days, then 2 mg tds for 3 days, then 1 mg bd for 3 days Xu et al, 2015 [24] Retrospective 26 Corticosteroid Local application of methylprednisolone sodium succinate after surgery Tanweer et al, 2016 [25] Retrospective analysis 14 Tranexamic acid Oral tranexamic acid 650 mg daily Hirashima et al, 2002 [26] Prospective case-control study 48 Etizolam 15 patients in etizolam group received 3.0 mg etizolam orally per day for 30 days after surgery…”
Section: Xuefuzhuyutangmentioning
confidence: 99%